Characterization of internal components and quality of red-winged tinamou (Rhynchotus rufescens) eggs throughout 28 d storage time (Research, Society and Development, 2021)
With the objective of characterizing the inner traits of red-winged tinamou (Rhynchotus rufescens) eggs at reproductive phase and evaluate the effects of the storage on quality indicators, a total of 50 eggs were distributed in a completely randomized design and kept at room temperature for 28 experimental days. Average egg weight, Haugh unit, yolk index, width and height of yolk, albumen height, pH of internal components and yolk color were evaluated. Yolk color scores were determined by direct method of chromatic traits (parameters of lightness (L) and chromaticity (a *) (b *)). Assessments were made on days 0, 10, 15, 21 and 28 after laying. During the experimental period there was a reduction (p